IoT-Based Wireless Battery Surveillance and Management System - Karthikeyen, S.; Priya, C. Kousi; Varshini, M.; Swathi, P.; Sudharsan, S. (Journal of Electronics and Informatics, 2024)
This research offers an Internet-of-Things (IoT) based battery surveillance machine for electric powered motors (EVs). The machine, is built using ESP32 microcontroller and Blynk IoT Cloud, to monitor the battery health in real-time. . The is equipped with sensors, to collects important facts along with voltage and charging styles. In case of faults, alerts are sent for prompt action. The ESP32 wirelessly transmits facts to the Blynk IoT Cloud platform, enabling the system to track and manage. Through a consumer-friendly interface, key parameters are visualized, facilitating proactive battery control. Additionally, the device offers Wi-Fi charging abilities through inductive coils, enhancing comfort. This included the capability to optimize EV battery overall performance and strengthen electric automobile technology.
Keywords: IoT; EV; Wireless Charging; Battery Surveillance